REGIONAL INEQUALITIES OF ECONOMIC AND RURAL DEVELOPMENT IN THE REPUBLIC OF SERBIA - Dimitrijevic, Jasmina; Dimitrijevic, Milos; Ristic, Lela (Economic Outlook, 2022)
Having in mind the fact that there are significant differences in the development of the regions in many countries, well-formulated regional policy and its implementation are important determinants of reducing existing regional inequalities and also they are the factors of rural development. Accordingly, the subject of research in this paper are disparities at the NUTS 2 level in the Republic of Serbia, with the aim of determining the level of economic development of the regions and the rural development of the Republic of Serbia. Thereby, an important role of regional policy in the regional convergence and achieving a more balanced regional and rural development is emphasized. The comparative analysis in the paper identifies significant differences between the Belgrade region and other regions in the Republic of Serbia, that are predominantly rural. In order to overcome these differences, the necessity of innovative solutions and an active regional policy is emphasized.
Keywords: regional development, rural development, regional policy, Nomenclature of Units for Territorial Statistics (NUTS)